Memahami Teologi Yohanes tentang Akhir Zaman - Daud Darmadi (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2019)
The end of the age has come, and now all believers are living in the last days. Many teachings about the end of time (eschatology) are currently circulating and developing. The differences in hermeneutic methods and methods of interpretation used have led to different teachings about theend times, some of which can be classified as unity. The church needs to have a solid theological basis of this exchatology, so that it is not easily swayed by various deceptions.The Apostle John, the writer of the Gospel of John, the three letters of John, and Revelation, talk a lot about the end of time, however, this paper needs to be reviewed so that it becomes a systematic and logical basis for the end times. Through the hermeneutic method, and exegetical analysis, theological themes about the end of time are produced. The second coming of Jesus explained will come as the King, the living God, the Just Judge. The issue of rapture is also one of the themes in John's theology, where at the coming of Jesus, the saints will be raptured. John's theology also describes the antichrist, which has existed since the early church opposed the true teachings of Jesus, and will continue to exist until the end of time. The doctrine of the millennium has shown various interpretations in John's writings, however, this thousand-year Kingdom speaks of God's absolute victory and power, and defeat of the devil. Abstrak IndonesiaAkhir zaman telah tiba, dan saat ini semua orang percaya sedang hidup dimasa akhir. Banyak ajaran tentang akhir zaman (Ekskatologi) yang saat ini sedang beredar dan berkembang. Perbedaan metode hermeneutik dan metode penafsiran yang digunakan telah membuahkan pengajaran tentang akhir zaman yang berbeda-beda, bahkan diantaranya ada yang dapat digolongkan sebagai penyesaan. Gereja perlu memiliki dasar teologi yang kokoh tentang ekskatologi ini, agar tidak mudah diombang-ambingkan oleh berbagai penyesatan. Rasul Yohanes penulis Injil Yohanes, ketiga surat Yohanes, dan Wahyu, banyak membicarakan akhir zaman, namun demikian tulisan ini perlu di kaji agar menjadi sebuah dasar pengetahuan tentang akhir zaman yang sistematis dan logis. Melalui metode hermeneutik, dan analisis eksegetis, maka dihasilkan tema-tema teologi tentang akhir zaman. Kedatangan Yesus yang kedua kali dijelaskan akan datang sebagai Raja, Allah yang hidup, Hakim yang Adil. Masalah pengangkatan juga menjadi salah satu tema dalam teologi Yohanes, dimana pada kedatangan Yesus, orang kudus akan diangkat. Teologi Yohanes juga menjelaskan tentang antikristus, yang sudah ada sejak gereja mula-mula yang menentang ajaran Yesus yang benar, dan akan terus ada sampai dengan akhir zaman. Ajaran tentang millennium, telah menunjukkan berbagai penafsiran dalam tulisan Yohanes, namun demikian Kerajaan seribu tahun ini berbicara tentang kemenangan dan kekuasaan Allah yang mutlak, dan kekalahan dari iblis.